2014
DOI: 10.1186/1471-2407-14-617
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phase I/II trial to Investigate Preoperative Dose-Escalated Intensity-Modulated Radiation Therapy (IMRT) and Intraoperative Radiation Therapy (IORT) in patients with retroperitoneal soft tissue sarcoma: interim analysis

Abstract: BackgroundTo report an unplanned interim analysis of a prospective, one-armed, single center phase I/II trial (NCT01566123).MethodsBetween 2007 and 2013, 27 patients (pts) with primary/recurrent retroperitoneal sarcomas (size > 5 cm, M0, at least marginally resectable) were enrolled. The protocol attempted neoadjuvant IMRT using an integrated boost with doses of 45–50 Gy to PTV and 50–56 Gy to GTV in 25 fractions, followed by surgery and IOERT (10–12 Gy). Primary endpoint was 5-year-LC, secondary endpoints inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 38 publications
0
56
1
9
Order By: Relevance
“…Surgical margins were negative for tumor cells by this approach, but it was very close (<1 mm). There have been some reports on the effectiveness of radiotherapy against local recurrence [6, 13, 14], while radiotherapy was reported to be a risk factor for LMS [15]. Adjuvant radiotherapy or chemotherapy was not performed because there is no established adjuvant therapy for rectal LMS and the elderly patient did not hope to receive adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical margins were negative for tumor cells by this approach, but it was very close (<1 mm). There have been some reports on the effectiveness of radiotherapy against local recurrence [6, 13, 14], while radiotherapy was reported to be a risk factor for LMS [15]. Adjuvant radiotherapy or chemotherapy was not performed because there is no established adjuvant therapy for rectal LMS and the elderly patient did not hope to receive adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneale Sarkome sind eine heterogene Gruppe von Tumoren mit unterschiedlicher Strahlensensibilität. Viele Studien setzen sich deshalb mit der Machbarkeit und den Ergebnissen von prä-, intra-und postoperativer Strahlentherapie bei RPS auseinander [2,20,26,30]. Aufgrund des Fehlens von randomisierten und prospektiven Studien kann keine allgemein gültige Aussage zur Stellung und Abfolge der Strahlentherapie getroffen werden, sie ist jedoch ein wichtiger Bestandteil und in der interdisziplinären Therapieplanung unbedingt zu diskutieren.…”
Section: Strahlentherapieunclassified
“…Compared to the postoperative approach, preoperative radiation therapy can offer several benefits, including a more precise target volume definition with smaller safety margins, reduced dose to adjacent organs at risk because of their displacement through the tumor itself, a possible devitalisation of tumor cells prior to surgery, fibrosis and thickening of the pseudocapsule, at least moderate tumor shrinkage and the avoidance of treatment delays due to postoperative complications [56, 58, 67]. This should result at least theoretically in less toxicity due to reduced doses in adjacent organs at risk but increased local control due to a more adequate target coverage which could be further enhanced by an intraoperative boost.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have evaluated combinations of preoperative and intraoperative radiation therapy and consistently reported high local control rates with acceptable toxicities (see Table 2) [57, 6773]. For example Petersen et al [57] reported the Mayo experience with 87 patients, who have been treated with preoperative EBRT (mainly 45–50 Gy) followed by maximal resection and IOERT (median dose 15 Gy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation